2020
DOI: 10.1021/acs.iecr.9b07044
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Fluid Flow Characteristics for Newtonian and Non-Newtonian Fluids in a Tube-in-Tube Helical Coil Heat Exchanger

Abstract: In the present work, heat transfer and fluid flow characteristics for both Newtonian and non-Newtonian fluids in tube-in-tube helical coil (TTHC) heat exchangers have been investigated numerically. The various TTHC heat exchanger configurations studied are (1) parallel and (2) counter flow, with and without baffles. The power law index (n) and Dean number (N De ) are varied from 0.5 to 1.25 and 50 to 500, respectively. Further, two different models have been proposed to predict the friction factor (f) and Nus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The coiled tubes heat exchangers and steam generators have many applications in different industries, including air conditioning 1 , 2 , chemical processes 3 5 , refrigeration 6 , nuclear 7 , 8 , and others. The main reason for using this type of heat exchanger is to improve the heat transfer coefficient due to the effects of centrifugal forces without additional energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…The coiled tubes heat exchangers and steam generators have many applications in different industries, including air conditioning 1 , 2 , chemical processes 3 5 , refrigeration 6 , nuclear 7 , 8 , and others. The main reason for using this type of heat exchanger is to improve the heat transfer coefficient due to the effects of centrifugal forces without additional energy sources.…”
Section: Introductionmentioning
confidence: 99%
“…This increases heat and mass transfer and leads to narrower residence time distributions. Although numerous studies were previously conducted to investigate the influence of different parameters on the advantages of helical pipes concerning heat and mass transfer (Gelfgat et al 2003;Kockmann 2020;Kurt et al 2015a, b;Kushwaha et al 2020;Liu et al 2005;Mei et al 2020;Mori and Nakayama 1965;Moulin et al 1996;Naphon and Wongwises 2006;Rainieri et al 2012;Rennie and Raghavan 2005;Schmidt 1967;Sedahmed et al 1985;Tohidi et al 2015;Yasuo and Wataru 1965), the characterization of pure mixing of miscible liquids in such apparatus, which is the fundament of the aforementioned transfer processes, has rarely been undertaken. The group of Nigam (Kumar et al 2006;Sharma et al 2017) investigated experimentally and numerically the influence of Reynolds number Re = (u ⋅ d ⋅ )∕ , Schmidt number Sc = ∕( ⋅ ab ) , and curvature ratio on the mixing performances of different coiled geometries, by determination of the residence time.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that pipe curvature, which creates a secondary flow, has a significant impact on flow amounts, whereas the torsion effect is smaller. Kushwaha et al [11] examined the heat transfer and fluid flow properties of Newtonian and non-Newtonian fluids in helical coil heat exchangers computationally. The results demonstrated that in helical coil heat exchanger with baffles in the annulus, f and Nu are greater than in a helix coil heat exchanger without baffles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the baffles have a substantial impact on heat transport at low Prandtl numbers. [11] Kurnia et al [12] found that adding twisted tape insert in helical heat exchanger can enhance heat transfer performance by up to four times as compared to traditional straight tube heat exchanger. The results of other practical experiments also indicated the possibility of increasing the heat transfer through the heat exchanger by inserting baffle in the heat exchanger shell-type coil [13].…”
Section: Introductionmentioning
confidence: 99%